2011
DOI: 10.1007/s12639-011-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

Control of poultry coccidiosis: changing trends

Abstract: Coccidiosis is the most important protozoan disease affecting the poultry industry worldwide. Control of poultry coccidiosis is presently based on managerial skills and the use of prophylactic coccidiostatic drugs. With the emergence of drug resistant Eimeria strains, emphasis has been laid on development and use of safer vaccines; some of them have been commercialized successfully. The present review deals with the various factors responsible for the development of clinical coccidiosis in poultry as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
49
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 56 publications
1
49
0
1
Order By: Relevance
“…Control of poultry coccidiosis is presently based on managerial skills and the use of prophylactic coccidiostatic drugs (Tewari and Maharana, 2011). It is a ubiquitous intestinal protozoan infection of poultry seriously impairing the growth and feed utilization of infected animals.…”
Section: Intruductionmentioning
confidence: 99%
“…Control of poultry coccidiosis is presently based on managerial skills and the use of prophylactic coccidiostatic drugs (Tewari and Maharana, 2011). It is a ubiquitous intestinal protozoan infection of poultry seriously impairing the growth and feed utilization of infected animals.…”
Section: Intruductionmentioning
confidence: 99%
“…They have developmental cycles with an exogenous phase in the environment and an endogenous phase in the intestine of chickens [3]. The efforts to prevent this disease have been focused on developing vaccines and drugs with coccidiostatic and coccidicidal activity [4]. So far, genomic studies have revealed the wide antigenic variability of species such as Eimeria tenella, one of the most pathogenic parasites to chickens, which leads to develop a vaccine resistance rapidly [1].…”
Section: Introductionmentioning
confidence: 99%
“…This infection is mostly asymptomatic and the response raised by the immune system pushes the parasite to differentiate into a slowly dividing, encysted form that persists for the life span of its host (Innes, 2010). Two other parasites of the phylum, Eimeria and Theileria spp., can cause economic losses affecting poultry and cattle, respectively (Bishop et al, 2004;Tewari and Maharana, 2011).…”
Section: Introductionmentioning
confidence: 99%